The relationship of personal budgets with independence, participation and quality of life; a secondary analysis of survey data using propensity score matching - Anna Maria Marangos; Jurjen Iedema; Mirjam de Klerk; Isolde Woittiez; Peter P. Groenewegen (SpringerOpen, 2020)
Abstract Objectives Personal budgets for social and health care have been introduced in many European countries over recent decades. The assumption is that people with a personal budget are able to purchase care that matches their needs more closely and therefore experience greater independence and improved well-being. The question is whether this assumption is true. Little research has been carried out on this and the research that has been carried out is inconclusive and hampered by methodological limitations. Methods We performed a secondary analysis of data collected in a survey among persons who had submitted an application for social support. Propensity score matching was used to investigate whether people with a personal budget experience better independence, participation in society and quality of life than comparable people using conventionally organised help. Results After matching, no significant effects of the personal budget were initially found. A sensitivity analysis that excluded the variable sense of mastery from the calculation of the propensity scores, showed a significantly greater independence for those using a personal budget. Conclusion There may be several reasons for this lack of effect. First, perhaps there are no effects. It is also possible that effects can only be found in specific situations and/or specific groups.